¿Es la práctica odontológica un trabajo social descontextualizado? - Carlos Payares-Gonzalez (Revista Facultad de Odontología Universidad de Antioquia, 1996)
Because of the discrimination suffered for the dentistry during the last century and enough time of the present century, this practice developed her knowledges like a "black box", whose technological foundation was undecipherable for the secular and another sanitary prctices. Around that time, the discrimination reverted in a monopoly, and the monopolyin a operative autonomy that facilitated the professionalism process. However, this circumstance, that was positive historically in order to a professionalism process, was negative in order to the scientific and academic foundations of the dentistry.